Beauty and the beast - Southgate, Vera (London : Lady bird Ltd)
In an enchanted castle, a beautiful, independent heroine encounters a monstrous beast. Although she becomes his prisoner, she sees the goodness deep within the Beast's hardened heart, and their friendship begins to blossom - all while an arrogant villain plot against them. Disney's Academy Award-winning Beauty and the Beast is a story of the powerful magic of love, and here you can relive that magic. Faithfully retold, with original, full-color artwork from the Disney film, here is a new classic - a tale as old as time.
Fiction English book
Keywords: English - Fiction Book